Pemilu Serentak dan Masa Depan Konsolidasi Demokrasi - Ria Casmi Arrsa (The Constitutional Court of the Republic of Indonesia, 2014)
The development of democracy in Indonesia is running very rapidly after the 1945 amendment. One of the developments within the frame of politics characterized by constitutional formula that provides a basic framework state that sovereignty belongs to the people and carried out in accordance with the Constitution. On the basis of the formulation of the succession of leadership in the executive and legislative branches are directly implemented as the mandate of Article 22 E of paragraph ( 2). However, in practice the constitutional arrangements in the Law Number 42 Year 2008 concerning General Pemlihan President and Vice President shows inconsistent with the statement in the constitution . As set out in Article 3 paragraph ( 5 ) states that the election of President and Vice- President held after an election DPR, DPD and DPRD. At the end of the Constitutional Court through Decision No. 14/PUU-XI/2013 stated that the selection of models is unconstitutional. Based on that assessment constitutionality of norms selection method based on the simultaneous interpretation of the constitution of both the original intent and interpretation of history. Design constitutional elections simultaneously referred born as an attempt to shift the direction of the transition towards democracy in the reinforcement system in order consolidation of democratic practice direct democracy tends opaque transactional, corrupt, manipulative, high costs and preserve power can be minimized in the practice of constitutional democracy dimention to understand and sovereignty of the people.